2020
DOI: 10.3389/fimmu.2019.03043
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Flow Induces the Postnatal Formation of Mature and Functional Meningeal Lymphatic Vessels

Abstract: Recently, the presence of lymphatics has been demonstrated and characterized in the dura mater, which is in contrast to the well-accepted view indicating the lack of a classical lymphatic drainage system of the central nervous system (CNS). Moreover, the role of meningeal lymphatics in the pathogenesis of Alzheimer's disease and multiple sclerosis was suggested. However, the possible regulators of the developmental program and function of meningeal lymphatics remain unclear. Here, we aimed at characterizing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…In fact, loss-of-function studies have shown that both the development and maintenance of adult meningeal LVs are dependent on VEGF-C signaling through VEGFR3, but not on VEGF-D signaling ( Antila et al, 2017 ). However, a more recent study has shown that mice lacking PLC-γ2 also present a structurally and functionally impaired meningeal lymphatic system, thus suggesting that meningeal lymphatic development might not be exclusively dependent on VEGFR3 signaling ( Bálint et al, 2020 ). Primordial meningeal LECs stem from and around the veins at the skull foramina and later extend from the basal into the lateral and dorsal meninges along the major arteries (pterygopalatine and middle meningeal arteries) and venous sinuses ( Aspelund et al, 2015 ; Antila et al, 2017 ; Izen et al, 2018 ; Ahn et al, 2019 ).…”
Section: Development Cytoarchitecture and Morphology Of Meningeal Lymphaticsmentioning
confidence: 99%
“…In fact, loss-of-function studies have shown that both the development and maintenance of adult meningeal LVs are dependent on VEGF-C signaling through VEGFR3, but not on VEGF-D signaling ( Antila et al, 2017 ). However, a more recent study has shown that mice lacking PLC-γ2 also present a structurally and functionally impaired meningeal lymphatic system, thus suggesting that meningeal lymphatic development might not be exclusively dependent on VEGFR3 signaling ( Bálint et al, 2020 ). Primordial meningeal LECs stem from and around the veins at the skull foramina and later extend from the basal into the lateral and dorsal meninges along the major arteries (pterygopalatine and middle meningeal arteries) and venous sinuses ( Aspelund et al, 2015 ; Antila et al, 2017 ; Izen et al, 2018 ; Ahn et al, 2019 ).…”
Section: Development Cytoarchitecture and Morphology Of Meningeal Lymphaticsmentioning
confidence: 99%
“…Lymph flow is reportedly reduced in mice with impaired PDPN/CLEC-2/PLCγ2 signaling [ 160 , 161 , 162 ] due to an improper separation of the blood and lymphatic vessel systems [ 156 ]. These data propose that these genetic mouse models provide ideal tools to study the roles of lymphatic flow in vivo.…”
Section: Importance Of Flow-induced Mechanical Forces In Lymphaticsmentioning
confidence: 99%
“…Importantly, while the formation of immature mesenteric pre-lymphatics is intact in mice with impaired lymph flow due to a lack of CLEC-2, organ-specific maturation of the mesenteric lymphatic vessels is impaired in these embryos [ 160 ], and the phenotype is also present in PLCγ2-deficient embryos [ 162 ]. In addition, the postnatal developmental program of the meningeal lymphatic vasculature is also affected in PLCγ2-deficient mice [ 162 ]. These in vivo findings underline the importance of mechanical forces in the organ-specific developmental program of the lymphatic vessels.…”
Section: Importance Of Flow-induced Mechanical Forces In Lymphaticsmentioning
confidence: 99%
“…To monitor lymphatic function pregnant Clp1 K/+ females timemated with Clp1 K/+ males were anesthetized. 0.5 µl of 70 kDa RhD (Life Technologies) at 10 mg/ml concentration was injected through the uterus and chest wall into the lung of E18.5 Clp1 K/K and littermate control embryos on Flt4 YFP lymphatic reporter background as described before (Jakus et al, 2014;Bálint et al, 2020). Selective uptake and transport of large molecular weight RhD in fluorescent reporter positive lymphatic vessels were monitored 60 min after the injection by a fluorescent Nikon SMZ25 stereomicroscope equipped with Nikon DS-Ri2 camera.…”
Section: Monitoring Pulmonary Lymphatic Function In Vivomentioning
confidence: 99%